ІNTEGRATION OF MODERN SACRED SPACE INTO HOSPITAL COMPLEXES: ARCHITECTURAL, PLANNING AND SOCIO-CULTURAL ASPECTS - Gnatiuk, Liliia (Theory and practice of design, 2025)
The article is devoted to the study of architectural and planning principles of integrating sacred spaces into complex functional complexes, in particular, large churches (such as chapels) and hospital institutions (as independent churches or chapels). Attention is focused on the functional-semantic conditioning of architectural solutions reflecting the spiritual needs of the congregation and the specific conditions of operation. Domestic and foreign examples demonstrating the evolution and typological variability of these architectural forms are analyzed. The purpose of the research to investigate the features of the formation of chapels and churches at hospitals as specific sacred spaces that perform the functions of spiritual support for patients, medical staff, and visitors in the context of modern medical architecture. Methodology. A comprehensive approach was used, including the analysis of architectural and functional features of chapels in various hospitals, the study of historical and modern trends in creating hospital sacred spaces, as well as a comparative analysis of European and Ukrainian examples. Methods of visual analysis, historical-architectural comparison, and socio-cultural interpretation were applied. Results. Key architectural features of chapels and churches in hospitals have been established that contribute to the creation of a zone of spiritual peace, support, and rehabilitation. Their spatial and symbolic significance in the context of the hospital environment, interaction with urban space, and influence on the psychological state of visitors are considered. Scientific novelty. For the first time, chapels and churches in hospitals are comprehensively considered as a special type of sacred space associated with a medical institution. New architectural and functional patterns have been identified that meet the needs of a modern medical facility and contribute to the integration of the culture of spirituality into the medical space. Practical relevance. The research results can be used in the design and reconstruction of hospital chapels and churches to enhance their functionality and emotional comfort for patients and staff, as well as in strategies for creating inclusive sacred environments in medical institutions.